JUAL-BELI TANAH PEKARANGAN DESA (PKD) (STUDI KASUS DI DESA PEKRAMAN PENESTANAN, KECAMATAN UBUD, KABUPATEN GIANYAR) - Adi Berry Kesuma Putra, Made; Oka Parwata, A.A. Gde; Ari Atu Dewi, A.A. Istri (Kertha Negara : Journal Ilmu Hukum; Vol. 01, No. 03, Mei 2013, 2013)
Land is very important in human life because the land is place where the humanborn, live, and do all activities community for their life. Rampant cases of land set in thesale of land, leasing land, seizure of land inheritance, sale of garden land to the villagebecome a problem. Linkage with such a man, according to Ter Haar said as perceivedaffinity and rooted in the minds of "all-pairs" (participeren Denden) it should beconsidered as "affinity laws" of human beings to the ground. Such a close relationshipbetween the law of the land under their control with a magical relationship religious naturethat causes people to obtain legal right to control the land, take advantage of it and collectthe results. From basic conception that the land under the control law based on theprinciple of solidarity alliances known in customary law.
Keywords: Land, Regulation, Village, Laws